Evaluation of the susceptibility to water erosion of a Soil vitric Haplustands, through the use of a rainfall minisimulator, in a hillside area of Colombia. - Mena, Hernán D.; Benavides, Cristian C; Castillo, Jesús A (Revista de Ciencias Agrícolas, 2011)
This research was conducted in the experimental farm FEDEPAPA located in the village of Obonuco in the municipality of Pasto, department of Nariño. The farm is located at 1 13’LN and 77 ° 16’LO to 2710 msnm with average annual rainfall of 840 mm and average temperature of 13 ° C, were was evaluated the susceptibility to water erosion in a Vitric haplustands land with a slope between 35 - 40%, using a portable rainfall minisimulator in four of land-use histories, which were located in all 12 land fields (product of 4 land use records for 3 plots or land fields in each). Rain simulations were conducted lasting 30 minutes within treatments (records) to determine the lamina infiltrated (mm), sheet runoff (mm) and the amount of eroded soil (t.ha-1). The research was conducted in four batches that have a handling history of several years, which are: 1. Pastures, 2. Potato, 3. Area without interference (ASI), 4. Secondary forest. The analysis of variance showed highly significant differences in the interactions of land use history over time. For the variable foil infiltration (mm) who presented a more stable behavior during the simulation was the forest history from 10 to 30 minutes with higher average values, with 2.31 mm and 2.59 mm respectively. In contrast to the treatment history pasture presented the lowest average values over time with 1.13 mm for 30 minutes. Regarding the variable sheet runoff (mm), who presented a more stable behavior during the simulation, was the forest history by recording the lowest average values with 0.090 mm and 0.389 mm. While the history pasture presented the highest average values with 0.072 mm and 1.73 mm. For variable soil eroded (t.ha-1) the treatment who reported lower losses was forest, who submitted the lowest average values from 5 to 30 minutes with 0.019 mm and 0.063 mm respectively. The highest average values for this variable are those presented by potato with 0.39 (t.ha-1) at 30 minutes of simulation ofrain.